PRAGMATIKANING TARKIBIY OMILLARI VA ULARNING MOLIYAVIY DISKURSDAGI NAMOYON BO‘LISHI (KONFERENSIYA, 2025)
The article examines the key components of pragmatics and its mechanisms that differ from semantics by relying on context, speaker intention, and the illocutionary and implicatural meanings of speech acts. Through the distinction between near-side and far-side pragmatics, the interpretation of indexicals, anaphora, and chains of reference is clarified. The study also analyzes the role of pragmatic factors in financial discourse, particularly their influence on market signals, investor behavior, and the institutional force encoded in communicative acts